Profiles of Achievement Motivation and Performance in Middle School: Links to Student Background and Perceived Classroom Climate - Erentaitė, Rasa; Vosylis, Rimantas; Sevalneva, Daiva; Melnikė, Eglė; Raižienė, Saulė; Daukantaitė, Daiva (Frontiers in Psychology, 2022)
Achievement motivation and performance at school are reciprocally related, however, empirical studies report a large variability of findings and, in some cases, weaker than expected associations between these constructs. To further our understanding of the motivation-performance link, we examined typical patterns of motivation and performance and their correlates, in two cohorts of 8th grade students (N1 = 998, N2 = 441). As expected, we identified both concordant and discordant patterns of achievement motivation and performance. In two subgroups, specifically, those characterized by low motivation and low performance (34% of the sample) and those characterized by high motivation and high performance (18% of the sample), the levels of motivation were highly concordant with scores on math and reading tests. In contrast, the other two profiles – weak motivation with elevated performance (38 % of all sample) and high motivation with low performance (9% of the sample) had divergent patterns of motivation and performance. The subgroups also differed on student socio-economic background, special educational needs, gender, as well as perceptions of classroom climate. Overall, our findings reveal context-dependent patterns of the relationship between aspects of achievement motivation and performance.